Hazel (Corylus avellana L.) leaves as source of antimicrobial and antioxidative compounds - Oliveira, Ivo (2007)
Aqueous extracts of leaves of different hazel (Corylus avellana L.) cultivars (Cv. M. Bollwiller, Fertille de Coutard and Daviana), were analysed by reversed-phase HPLC/DAD for the definition of their phenolic composition. Antioxidant potential was assessed by the reducing power assay, and the scavenging effect on DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and b-carotene linoleate model system. Their antimicrobial capacity was also tested against Gram positive (Bacillus cereus, Bacillus subtilis, Staphylococcus aureus) and Gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae) and fungi (Candida albicans, Cryptococcus neoformans). Eight phenolic compounds were identified: 3-, 4- and 5-caffeoylquinic acids, caffeoyltartaric acid, p-coumaroyltartaric acid, myricetin-rhamnoside, quercetin 3-rhamnoside and kaempferol 3-rhamnoside. A p-coumaric acid, three myricetin and one quercetin derivatives were also detected. The hazel leaves extract presented high antioxidant activity in a concentration-dependent way, in general with similar behaviour of all cultivars. Gram positive bacteria revealed to be very sensitive to hazel leaf extract (MIC 0.1 mg/ml for B. cereus and S. aureus and 1 mg/ml for B. subtilis). However, Gram negative and the fungi displayed much lower sensitivity, being P. aeruginosa and C. albicans resistant at 100 mg/ml. Cv. M. Bollwiller exhibited the most potent antimicrobial activity.